Structural Proteins of Simian Virus 40 - Barban, Stanley (1971)
Sodium dodecyl sulfate acrylamide gel electrophoresis of the solubilized proteins from purified simian virus 40 (SV40) virions revealed two major and two minor structural polypeptide components. The major components which comprise over 75% of the total virion were shown to be the capsid proteins by immunological and isoelectric focusing fractionation analysis. These two polypeptides have estimated molecular weights of 45,000 daltons as determined by gel electrophoresis. One of the two minor components was identified as the nucleocapsid protein and has an approximate molecular weight of 16,000. The other unidentified minor component has an average molecular weight of 29,000.